The Cache Based Scheme To Increase Lifetime of Wireless Sensor Networks - Verma, Disha; Rawat, Sandeep Kumar (International Journal of Computer Sciences and Engineering, 2019)
The wireless sensor networks is the decentralized type of network in which sensor nodes join or leave the when they want. The energy consumption is the major issue of wireless sensor networks due to small size and far deployment of the sensor nodes. The whole network is divided into fixed size clusters and cluster heads are selected in each cluster based on distance and energy. The hierarchal routing is the efficient technique for the data aggregation which uses least network energy. The TH-leach is the improved version of LEACH protocol to increase lifetime of the sensor network. In this research work, the TH-leach routing protocol will be further improved to increase one level to improve lifetime of the network.